Motivated Reasoning and Attitudes Towards Supreme Court Confirmation Hearings: Evidence from Five Nominations and an Experiment. (June 2023) - Badas, Alex
Relying on theories of motivated reasoning, I hypothesize that individuals who favor a nominee will prefer a legalistic confirmation hearing, while those who oppose a nominee will prefer a politicized confirmation hearing. Analyzing survey data from five recent nominees and a survey experiment, I find support for this hypothesis. The results have implications for how the public interacts with the nature of the Court's hybrid institutional structure. Specifically, I argue the results support the notion that the public engages in a political calculation when making judgements about the Court. When it serves their preferences, people will view the Court as a legalistic institution; however, when individuals believe there is an advantage in viewing the Court as a political institution, they are more likely to desire the Court to be evaluated in political ways.